ANALISIS KEMAMPUAN KONEKSI MATEMATIK SISWA MTS DITINJAU DARI SELF REGULATED LEARNING - Hadin, Hadin; Pauji, Helmy Muhammad; Aripin, Usman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to describe the extent to which the mathematical connection ability of students who viewed from Self Regulated Learning seen from students' mistakes in solving a problem of mathematical connection ability. The subject of this study students Classes VIIIA MTs AL-Hikmah Talegong Garut II as many as 20 students. The method used in this research is a descriptive method with quantitative approach. The research stage consisted of 4 stages, among others: self-regulated learning questionnaires, tests of mathematical connection ability, data analysis and draw conclusions. The results of the research were obtained that 1) Students who have high learning independence make mistakes on inter-topic relationships in mathematics and apply/use mathematics in other fields or in everyday life, 2) Students who have learning independence are making mistakes in understanding relationships between topics in mathematics as well as in identifying processes or procedures in carrying out basic concepts, 3) Students have low self-reliance to make mistakes in understanding the relationship of mathematics in other fields of science or in everyday life. Based on the results of the study can be concluded that the better the students' independence in learning then the smaller make a mistake in solve the problem of mathematical connection capabilities.